A task scheduling algorithm for cloud computing with resource reservation. Issue 5 (4th May 2023) - Sung, Inkyung; Choi, Bongjun; Nielsen, Peter
Abstract : Resource-reservation-based services have been provided where cloud resources are reserved for tasks within specific time intervals so as fully to exploit the benefits of cloud computing. Such a practice induces an additional decision for task allocation timing and a time index to resource status. Combined with the increasing scale of cloud computing, this increases the complexity of task scheduling in cloud computing. On the other hand, the quality and responsiveness of a task scheduling process should be pursued to meet the desired service features of the market. A task scheduling problem with time-dependent resource availability is formulated, and an heuristic algorithm that derives a high-quality solution to the problem within a very short time is designed to address these challenges. The performance of the algorithm in terms of its optimality and computation efficiency is demonstrated by comparison with the optimal bound found by a commercial optimization solver.